Limb activation ameliorates body-related deficits in spatial neglect - Reinhart, Stefan; Schmidt, Lena; Kuhn, Caroline; Schenk, Thomas; Keller, Ingo; Kerkhoff, Georg (Frontiers in Human Neuroscience, 2012)
Abstract: Many neglect patients show deficits in the mental representation of their contralesional body side or body parts, termed personal neglect. These deficits include impairments in identifying body parts on schematic drawings of human bodies. Limb activation and alertness cues have been shown to modulate neglect transiently, and are effective treatments for several symptoms of the neglect syndrome. Here, we tested on 8 patients with right-hemispheric stroke and left-sided spatial neglect whether these two techniques modulate deficits in the mental representation of hands, assessed with a hand-test in which the subjects had to decide whether a depicted schematic hand belongs to the left or right side of the human body. The results showed that neglect patients made marginally significant (p = 0.065) more errors in left-hand-decisions than right-hand-decisions, indicating a neglect-specific disorder. Moreover, we found that left-sided limb activation but not nonlateralized alertness cueing (a loud noise immediately before patients made their perceptual decision) significantly reduced misidentifications for depicted left hands as compared to baseline. No effect of any intervention was observed on error rates for depicted right hands. We conclude that the amelioration of the performance in the hand task is modulated by the activation of the body schema or other body representations through left-sided limb activation.